Intraoperative modulation of arterial blood flow in a hybrid operating room: A report of three cases. Issue 10 (15th August 2019) - Saitoh, Yoshikatsu; Hara, Yasuyuki; Miyagi, Shigehito; Nakanishi, Chikashi; Nakanishi, Wataru; Nishimura, Ryuichi; Akamatsu, Daijirou; Goto, Hitoshi; Unno, Michiaki; Kamei, Takashi
Abstract: The preoperative modulation of arterial blood flow is widely performed to prevent massive intraoperative hemorrhage and unstable circulatory dynamics; however, this may cause complications. The intraoperative modulation of arterial blood flow can be performed with operation to reduce the physical and psychological stresses on the patients and improve intraoperative safety. Abstract : The preoperative modulation of arterial blood flow is widely performed to prevent massive intraoperative hemorrhage and unstable circulatory dynamics; however, this may cause complications. The intraoperative modulation of arterial blood flow can be performed with operation to reduce the physical and psychological stresses on the patients and improve intraoperative safety.